Controversial issues of nomenclature and terminology of calcium pyrophosphate crystal deposition disease - M. S. Eliseev; E. L. Nasonov (Научно-практическая ревматология)
Since the discovery in the early 1960s by D.J. McCarty crystals of calcium pyrophosphate in the synovial fluid of a patient with suspected gout, descriptions by D. Zitnan and S. Sitaj of radiological signs of cartilage calcification, and the subsequent appearance of the terms “pseudogout” and chondrocalcinosis, up to the present time, the issue of standardization of terms and concepts related to the disease of conditions and symptoms has not been resolved. The various alternative names of the disease and classification of phenotypes considered in the article should be the basis for creating a unified nomenclature of the disease of deposition of calcium pyrophosphate crystals, reflect the essence of the disease, and be understandable to doctors and patients.